Mineralogy and Geochemistry of Gold Ore Low Sulfidation -Epithermal at Lamuntet, Brang Rea, West Sumbawa District, West Nusa Tenggara Province - Rika Ernawati; Arifudin Idrus; Himawan Tri Bayu Murti Petrus (Journal of Geoscience, Engineering, Environment, and Technology, 2019)
There are two Artisanal Small scale Gold Mining (ASGM) location in Lamuntet, Brang Rea Subdistrict, West Nusa Tenggara Regency, namely Nglampar and Song location. Nglampar and Song location are included in the low sulfidation epithermal gold deposit system. The research purposes to analyze mineralogy and geochemistry of gold vein deposits and determine system of low sulfidation gold ore in Nglampar, Lamuntet Village. The methods used to determine the mineralogy of gold vein deposits are petrography, mineragraphy and X-ray diffractometer (XRD) analysis, while geochemical analysis using Scanning Electron Microscope (SEM) with Energy Dispersive X-Ray Spectroscopy (EDS), Fire Assay (FA) and Atomic Absorption Spectrophotometry (AAS). The results showed that the minerals contained were quartz (Qz), sericite (Ser), Chalcedon (Chc), chlorite (Chl), pyrite (Py), sphalerite (Sph), galena (Gn) , gold (Au), chalcopyrite (Cp), argentite (Ag), arsenopyrite (Apy), Azurit (Az), Malakit (Mal) and bornite (Bn). Abundant mineral availability such as sphalerite, galena, chalcopyrite and arsenopyrite are characterized by high levels of Zn, Pb, Cu and As the metal in vein deposits. This can be seen on the chemical content of ore in gold vein deposits ie Au 0.1 ppm -27.8 ppm, Ag 3 ppm-185 ppm, Pb 101 ppm - 35,800 ppm, Zn 73 ppm-60,200 ppm, Cu 26 ppm - 1,740 ppm, and As 150 ppm - 6,530 ppm. Based on the results of SEM-EDS analysis shows that the type of gold mineral is the electrum because of the content of Ag> 20%. Based on those characteristics of the mineralogy and geochemistry in this study showed that low sulfidation gold ore in this area is categorized as polymetallic gold-silver system.